Las formas de la verdad : investigación, docuficción y memoria en la novela hispánica (2000-2015) - Martínez Rubio, José, 1985- (Autores, textos y temas. Literatura, 2015)
This volume analyzes novels written in Spain and Latin America between 2000 and 2015. Apart from literature, psychoanalysis, philosophy, sociology, and cultural history, this text helps address phenomena such as docudrama, the cultural need for reality, and identity creation.